INFLUENCE MOTIVATION ACHIEVMENT AGAINST MINDSET ENTREPRENEURSHIP IN STUDENTS MAKASSAR STATE UNIVERSITY FACULTY OF ECONOMICS - Sumiati Tahir; Agus Syam; Muhammad Ilyas Thamrin Tahir (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The purpose of this study is to ascertain how accomplishment motivation affects students at Makassar State University’s Faculty of Economics with regard to their entrepreneurial attitude. A sample of one hundred students was taken using the Probability Sampling approach. Primary data, or information obtained directly from respondents via surveys, and secondary data were the methods used to acquire the data. A questionnaire was employed in the data-gathering process. Simple regression analysis was conducted using SPSS as the data analysis tool. The study’s findings indicate that accomplishment motivation had a direct, favorable, and significant impact on the entrepreneurial attitude.